An interpretive phenomenological analysis of cricket coaches' experience of a Mindfulness-Acceptance-Commitment (MAC) approach to coaching - Steyn, Barend Johannes Marthinus (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.